Lessons learned from child health care nurses' experiences of teaching infant massage groups: A qualitative interview‐based study - Josefin A. Isaksson; Gerth Hedov; Pernilla Garmy (Wiley, 2023)
Abstract Aim To describe child health care nurses' experiences of teaching infant massage in parent groups. Design This was an exploratory‐descriptive qualitative study based on individual interviews. Method Qualitative semi‐structured interviews were conducted with child health care nurses (N = 9) according to the COREQ guidelines and analyzed with qualitative content analysis. Results Five categories were identified: (1) Infant massage can promote attachment between parents/guardians and their children; (2) Infant massage can have a calming impact; (3) Stress and lack of time can be challenging; (4) The composition of parent groups can be important and (5) The child health care nurse can observe parents'/guardians' relationships with their children. Child health care nurses are uniquely familiar with infant massage and the benefits it provides both parents/guardians and their infants. Specifically, infant massage has a calming effect that reduces stress and strengthens the relationship between infants and their parents/guardians. Patient or Public Contribution Child health care nurses were interviewed.